Humanitarian Contexts of Technical Education in Russia - A. L. Andreev (Высшее образование в России)
The article deals with the problem of formation of social and humanitarian competen[1]cies in Russian engineering education. The author shows how different views on the relationship between man and machine, as well as between society and the technosphere, were translated into various public initiatives and analyzes the impact of these initiatives on the evolution of approaches to engineering education. Special attention is paid to the promotion of the ideology of design think[1]ing and the movement for the humanitarization of engineering education. Both gained a consider[1]able popularity in the last quarter of the twentieth century. However, in modern conditions, the relationship between technological progress and the development of human society is taking on new forms that require new answers. There are also new risks – in particular, the risk of complete de[1]humanization of technological progress and the unclear prospect of the formation of a so-called post-human civilization. Social assessment of technology and the development of value-based tech[1]nologies are possible answers. They have received a very significant support in the United States and Western Europe. In particular, several European conferences on this topic have already been held within the EU (the latest one took place in Bratislava in 2019). However, due to some features of the Russian intellectual tradition, as well as the pronounced techno-optimism of mass consciousness, the Russian academic environment has not yet shown sufficient interest to implant these approaches in technical education. The possibility of managing the current technological progress on the basis of a dialogue with civil society, which is popular in the European Union, is also not considered in Russian intellectual environments. At the same time, the leading technical universities in Russia are gradually developing a network of enthusiasts who are studying the European practice of social assessment of technology and its adaptation to Russian conditions. Such adapted practices may become the con[1]ceptual guidelines for Russian engineering education.